2014
DOI: 10.3389/fonc.2014.00366
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Understanding of Multiscale Tumor Heterogeneity

Abstract: Cancer is a multifaceted disease characterized by heterogeneous genetic alterations and cellular metabolism, at the organ, tissue, and cellular level. Key features of cancer heterogeneity are summarized by 10 acquired capabilities, which govern malignant transformation and progression of invasive tumors. The relative contribution of these hallmark features to the disease process varies between cancers. At the DNA and cellular level, germ-line and somatic gene mutations are found across all cancer types, causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 127 publications
1
70
0
2
Order By: Relevance
“…The differential sensitivity to drugs by subpopulations of cells, or cells of different types, can provide an indication of compound mechanism of action [2, 7-9, 12, 13, 66] 1 . In one study it was shown that cells treated with drugs of similar mechanism of action induce similar heterogeneity [64], while in another study, the analysis of the heterogeneity induced by a drug led to the development of a hypothesis of interacting networks [61].…”
Section: Discussionmentioning
confidence: 99%
“…The differential sensitivity to drugs by subpopulations of cells, or cells of different types, can provide an indication of compound mechanism of action [2, 7-9, 12, 13, 66] 1 . In one study it was shown that cells treated with drugs of similar mechanism of action induce similar heterogeneity [64], while in another study, the analysis of the heterogeneity induced by a drug led to the development of a hypothesis of interacting networks [61].…”
Section: Discussionmentioning
confidence: 99%
“…This microenvironment, which defines an additional barrier or an asset for therapy, is responsible for differently directed selective pressure within the same tumour, changing the evolutional trajectories of the tumour cells [118]. This opens up new areas of research for developing techniques focusing on regulating the tumour microenvironment in order to control tumour progression.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…4, 68 The differential sensitivity to drug treatment of subpopulations of cells may well provide an indication of compound mechanism(s) of action. 1, 5, 9, 64, 65, 68, 69 Differential sensitivity measurements in vitro also provide insights into how effective a therapy might be in vivo . For example, if the half-maximal response represents all cells showing 50% inhibition, then treatment cycles in vivo may produce a different response rate than if the half maximal response is a result of 100% inhibition in half of the cells.…”
Section: Introduction: Biological Heterogeneity Is a Fundamental Propmentioning
confidence: 99%